Clinical Features and Prognosis Of Coronary Heart Disease In Patients With Metabolic Syndrome (Texas Journal of Medical Science, 2024)
Cardiovascular diseases (CVDs) are the leading cause of disability and death worldwide. In 2020, the WHO reported in Geneva that 17.3 million people died from CVDs, accounting for 30% of all deaths worldwide (WHO report, 2020). Of this number, 7.3 million people died from complications of coronary artery disease (CHD) (World Health Organization, 2021). The study of coronary artery disease, its complications and the effectiveness of treatment dictates the need to study risk factors. It is known that metabolic disorders such as excess body weight, dyslipidemia and impaired glucose metabolism accelerate atherogenesis. All these disorders are components of metabolic syndrome (MS). The issue of the effect of MS on the cardiovascular system has been studied in sufficient detail in the literature, however, the effect of the syndrome on the results of angioplasty procedures and long-term prognosis of coronary artery disease requires further study.